1998
DOI: 10.1046/j.1365-2567.1998.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of mRNA stability in the different patterns of cytokine production by CD4+ cells from young and old mice

Abstract: SUMMARYCD4+ cells from young (3 months) and old (19 months) mice were stimulated by plate-bound anti-CD3 monoclonal antibody (mAb) alone or also by soluble anti-CD28 mAb. Supernatants were analysed by enzyme-linked immunosorbent assay ( ELISA) to determine cytokine concentrations. Total RNA was extracted from cells, reverse transcribed and the cDNA amplified by polymerase chain reaction (PCR) to evaluate the amount of specific mRNA. The results indicate that anti-CD3 alone is not sufficient to induce interleuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Stabilization of ARE-mRNA is mainly controlled by p38 MAPK, ERK, and PI3K signaling pathways, which can be all activated following the CD28 ligation (22)(23)(24)(25). Several other mRNA cytokine messages such as for IFN-␥, IL-4, and IL-10 are stabilized in CD4 T cells by CD28 stimulation (26).…”
Section: T He "Professional" Cd4mentioning
confidence: 99%
“…Stabilization of ARE-mRNA is mainly controlled by p38 MAPK, ERK, and PI3K signaling pathways, which can be all activated following the CD28 ligation (22)(23)(24)(25). Several other mRNA cytokine messages such as for IFN-␥, IL-4, and IL-10 are stabilized in CD4 T cells by CD28 stimulation (26).…”
Section: T He "Professional" Cd4mentioning
confidence: 99%
“…The reason for the accumulation of T reg cells in old mice is not yet understood. It has been demonstrated that there is shift from a Th1 to a Th2 response in aged mice (35), with an increased production of IL-10 (36), which may account in part for the high accumulation of T reg cells in these animals. Further studies are needed to completely understand the reason that T reg cells accumulate or expand in the old and how these populations relate to other immune-regulatory effects, such as cytokines, homeostasis, and APCs, and determine their specificity.…”
Section: Foxp3 Also Called Scurfin Belongs To the Forkhead Family Omentioning
confidence: 99%
“…Cytokines were titrated in culture supernatants by sandwich ELISA as already described (Pioli et al, 1998). The reference straight line obtained by plotting the absorbance versus the standard cytokine concentrations was used to calculate cytokine concentrations in the supernatants.…”
Section: Cytokine Titrationmentioning
confidence: 99%